2017
DOI: 10.1038/cddiscovery.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytokine withdrawal-induced death sensitivity of effector T cells derived from distinct human CD8+ memory subsets

Abstract: CD8+ central memory (CM) and effector memory (EM) T-cell subsets exhibit well-established differences in proliferative and protective capacity after infectious challenge. However, their relative sensitivity to apoptosis has been largely overlooked, despite the importance of programmed cell death in regulating effector T-cell homeostasis. Here we demonstrate that primary human effector T cells derived from the CD8+ EM subset exhibit significantly higher sensitivity to cytokine withdrawal-induced cell death (CWI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…During the contraction phase of the T cell response triggered by cytokine withdrawal, T cells also increase autophagic activity to cope with the stress of growth factor deprivation [43, 44]. Macroautophagy, referred to here as autophagy, is a catabolic process by which cellular proteins and organelles are degraded to provide free amino acids and allows T cells to maintain ATP production.…”
Section: T Cell Metabolism and Death Sensitivity Can Influence Immunomentioning
confidence: 99%
See 3 more Smart Citations
“…During the contraction phase of the T cell response triggered by cytokine withdrawal, T cells also increase autophagic activity to cope with the stress of growth factor deprivation [43, 44]. Macroautophagy, referred to here as autophagy, is a catabolic process by which cellular proteins and organelles are degraded to provide free amino acids and allows T cells to maintain ATP production.…”
Section: T Cell Metabolism and Death Sensitivity Can Influence Immunomentioning
confidence: 99%
“…Inhibition of NOTCH1 signaling induces metabolic shutdown and triggers autophagy for survival in T cell acute lymphoblastic leukemia (T-ALL); co-inhibition of autophagy synergistically enhanced anti-NOTCH treatment efficacy in eliminating T-ALL cells [52]. Additionally, we recently demonstrated that secondary effector T cells derived from sorted human memory CD8 + T cell subsets (central and effector memory) are differentially sensitive to CWID [43]. Effectors derived from the central memory (CM) pool are more resistant to RICD than their effector memory (EM)-derived counterparts, due to more sustained protective autophagy and reduced BIM expression [43].…”
Section: T Cell Metabolism and Death Sensitivity Can Influence Immunomentioning
confidence: 99%
See 2 more Smart Citations
“…IL2 complexes also stabilize the expression of the Treg-lineage master transcription factor, FOXP3 in TGF-B-induced pTregs 30 . We hypothesized that ex-vivo expanded Tregs' exposure to high IL2 concentrations may render them particularly sensitive to cytokine withdrawalinduced death 31 (CWID) after adoptive transfer, a sensitivity that could be ameliorated with systemic IL2 therapy. Given proven IL2 and rapamycin (IL2+rapa) advantages in supporting endogenous Treg expansion in small animal models 32,33 and patients 34 , we tested IL2+rapa for its capacity to prolong the half-life of autologously-derived, ex-vivoexpanded Tregs after adoptive transfer in an outbred, NHP model and performed flow cytometry and single cell transcriptomics to explore underlying mechanisms and correlations with lifespan and Treg subset dynamics after transfer.…”
Section: Introductionmentioning
confidence: 99%